Anticoagulation in patients with atrial fibrillation undergoing coronary stent implantation - Bernard, Anne; Fauchier, Laurent; Pellegrin, Céline; Clementy, Nicolas; Etienne, Christophe Saint; Banerjee, Amitava; Naudin, Djedjiga; Angoulvant, Denis (Thrombosis and Haemostasis, 2013)
In patients with atrial fibrillation (AF) undergoing coronary stent implantation, the optimal antithrombotic strategy is unclear. We evaluated whether use of oral anticoagulation (OAC) was associated with any benefit in morbidity or mortality in patients with AF, high risk of thromboembolism (TE) (CHA2DS2-VASC score ≥2) and coronary stent implantation. Among 8,962 unselected patients with AF seen between 2000 and 2010, a total of 2,709 (30%) had coronary artery disease and 417/2,709 (15%) underwent stent implantation while having CHA2DS2-VASC score ≥2. During follow-up (median=650 days), all TE, bleeding episodes, and major adverse cardiac events (i.e. death, acute myocardial infarction, target lesion revascularisation) were recorded. At discharge, 97/417 patients (23%) received OAC, which was more likely to be prescribed in patients with permanent AF and in those treated for elective stent implantation. The incidence of outcome event rates was not significantly different in patients treated and those not treated with OAC. However, in multivariate analysis, the lack of OAC at discharge was independently associated with increased risk of death/stroke/systemic TE (relative risk [RR] =2.18, 95% confidence interval [CI] 1.02-4.67, p=0.04), with older age (RR =1.12, 1.04-1.20, p=0.003), heart failure (RR =3.26, 1.18-9.01, p=0.02), and history of stroke (RR =18.87, 3.11-111.11, p=0.001). In conclusion, in patients with AF and high thromboembolic risk after stent implantation, use of OAC was independently associated with decreased risk of subsequent death/stroke/systemic TE, suggesting that OAC should be systematically used in this patient population.
Keywords: Atrial fibrillation; oral anticoagulant; antiplatelet agent; coronary stent implantation